Low-Dose Ketamine and Propofol Combination for Upper Endoscopy in Morbidly Obese Patients - Hosni A Salem (Global Journal of Anesthesiology - Peertechz Publications, 2017)
Aim: The purpose of this randomized double-blinded study is to compare the safety and efficacy of two different concentrations of ketofol on the intraoperative hemodynamics, respiration, bispectral index values and post-anesthesia recovery profiles in morbid obese patients undergoing upper GI endoscopy.  Subjects and methods: Patients were randomly allocated into two groups, group I (k/p 1/2), no = 50, and group II (k/p 1/4), no = 50, after receiving ethics committee approval and informed patient's consent. Patients in group I received bolus dose of ketamine 0.5 mg/kg + propofol 1 mg/kg, and group II received ketamine 0.25 mg/kg + propofol 1 mg/kg, intravenously in separate syringes (dosed ketamine then propofol). Incremental doses, half the fi rst dose of propofol (0.5 mg/kg) were given to get the desired depth of sedation, modifi ed by aiming at bispectral index (BIS) values between 70-80, and when the sedation was considered as inadequate by the endoscopist. The baseline measurements were obtained just before the administration of the study drugs. The primary outcome was emergence reactions (recovery agitation or hallucination) following the procedure. Results: There was no signifi cant difference between group I (k/p 1/2) and group II (k/p 1/4) as regard to demographic data (age, gender and BMI) and procedure duration. Discharge time from postanesthesia care unit (PACU) was prolonged in group I (Mean±SD = 38.34±4.28) compared to group II (Mean±SD = 33.11±4.89), p = 0.0001. The number of patients requiring propofol top-up doses was 20 (40%) in group I compared to 35 (70%) in group II (the low-dose ketamine group), p = 0.004. There was a significant difference in the mean propofol top-up dose between the two groups (30±15 mg in group I and 41±13 mg in group II, p = 0.0002). No signifi cant difference between both groups as regard to BIS values and VAS pain score. Conclusion: The use of ketamine and propofol combination for upper GI endoscopy in morbid obese patients appears to be safe, effective and preserve the hemodynamic and respiratory parameters.